Anti‐MDA5 antibody‐positive clinically amyopathic dermatomyositis with diffuse alveolar damage diagnosed by transbronchial lung cryobiopsy: A case report. Issue 11 (19th October 2021) - Ishihara, Hiroyuki; Kataoka, Kensuke; Takei, Reoto; Yamano, Yasuhiko; Yokoyama, Toshiki; Matsuda, Toshiaki; Kimura, Tomoki; Fukuoka, Junya; Johkoh, Takeshi; Kondoh, Yasuhiro
Abstract: Diffuse alveolar damage (DAD) is known to be a pathological hallmark of acute respiratory distress syndrome or acute interstitial pneumonia, and to have a poor prognosis. We report a case of anti‐melanoma differentiation‐associated gene 5 (MDA5) antibody‐positive clinically amyopathic dermatomyositis (CADM) with rapidly progressive interstitial lung disease (RP‐ILD), in which DAD was confirmed by transbronchial lung cryobiopsy at an early stage without respiratory failure. Although this patient initially did not show respiratory failure, his respiratory condition gradually worsened despite intensive immunosuppression therapy and he died 3 months later. Therefore, the early pathological findings of DAD did not match the clinical picture, which showed no respiratory failure. However, these findings were consistent with the subsequent course and poor outcome. Histological DAD, even in the absence of respiratory failure, may indicate a subsequent poor prognosis and explain the refractory course of RP‐ILD with anti‐MDA5 antibody‐positive CADM. Abstract : We report a case showing diffuse alveolar damage in a patient with rapidly progressive interstitial lung disease (RP‐ILD) with anti‐melanoma differentiation‐associated gene 5 antibody‐positive clinically amyopathic dermatomyositis, diagnosed by transbronchial lung cryobiopsy (TBLC) at an early stage without respiratory failure. Although this patient initially did not show respiratory failure, his respiratory condition gradually worsened despite intensive immunosuppression therapy and he died 3 months later. In patients with RP‐ILD, TBLC has the potential to predict prognosis and treatment response by evaluating the pathological pattern.